Implementation of the Problem Based Learning Model Using Pancasila Smart Board Media to Improve Learning Outcomes of Elementary School Students - Haura Chaerunisa; Dianasari Dianasari; Hanikah Hanikah (FKIP - Universitas Riau, 2026)
This study aimed to improve students' learning outcomes through the implementation of the Problem Based Learning model supported by the Pancasila Smart Board in Pancasila Education for third-grade students at SDN 2 Patapan. This study employed Classroom Action Research (CAR) based on the model proposed by Kemmis and McTaggart. The findings indicated that students' learning outcomes improved progressively through the implementation of actions in each research cycle. In the pre-cycle, only 16.67% of students achieved the learning mastery criteria. Following the implementation of the actions in Cycle I, the percentage of students achieving learning mastery increased to 45.83%. However, this result had not yet met the predetermined success indicators; therefore, improvements to the instructional actions were made based on the reflection results before proceeding to Cycle II. After implementing the revised actions in Cycle II, the percentage of students achieving learning mastery increased to 87.50%, indicating that the predetermined success indicators had been achieved. In conclusion, the implementation of the Problem Based Learning model supported by the Pancasila Smart Board effectively improved the learning outcomes of third-grade students in Pancasila Education at SDN 2 Patapan.